+0  
 
0
1006
2
avatar

y-3x=5 2x=3y+6

 Jun 5, 2014

Best Answer 

 #1
avatar+3451 
+5

y-3x=5 | 2x=3y+6

y=3x+5

 

|

|

V

2x=3(3x+5) + 6

2x=9x+15+6

     -9x

-7x=21

-(-7x=21)

7x = -21

x = -3

 

y-3(-3)=5

y-(-9)=5

y+9 = 5

  -9    -9

y= -4

 

So, y= -4 and x = -3

 

Let's check it:

y-3x=5 

(-4) - 3(-3) = 5

-4 - (-9) = 5

-4 +9 = 5

5=5 ✔

 Jun 5, 2014
 #1
avatar+3451 
+5
Best Answer

y-3x=5 | 2x=3y+6

y=3x+5

 

|

|

V

2x=3(3x+5) + 6

2x=9x+15+6

     -9x

-7x=21

-(-7x=21)

7x = -21

x = -3

 

y-3(-3)=5

y-(-9)=5

y+9 = 5

  -9    -9

y= -4

 

So, y= -4 and x = -3

 

Let's check it:

y-3x=5 

(-4) - 3(-3) = 5

-4 - (-9) = 5

-4 +9 = 5

5=5 ✔

NinjaDevo Jun 5, 2014
 #2
avatar+114434 
0

Great job, NinjaDevo......well presented, too...Thumbs Up and Points......!!!!

 

 Jun 5, 2014

72 Online Users

avatar
avatar
avatar
avatar